A STUDY ON CUSTOMER PERCEPTION TOWARDS MOBILE- WALLET AMONG YOUTH WITH SPECIAL REFERENCE TO COIMBATORE CITY (GPAY & PHONEPE) - K., Mirunalini; S., Murugan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
According to the examine it seems that many human beings truly consider the authorities at the usefulness of cashless financial system because it enables to combat towards terrorism, corruption, cash laundering however one largest hassle with inside the running of cashless financial system in India is cybercrime and unlawful get right of entry to number one facts. It became observed that demographic component anticipate schooling does now no longer have a good deal effect at the adoption of the virtual fee. It shows that adoption of virtual fee is inspired through the instructional degree of the Payments. The increase of customers of clever telecast smartphone and net penetration in such location additionally facilitated the adoption of virtual fee.